An innovative 3D-CFD-approach towards virtual development of internal combustion engines - Chiodi, Marco (Springer eBooks., 2011)
In the engine development process, simulation and predictive programs have continuously gained in reliance. Due to the complexity of future internal combustion engines the application of simulation programs towards a reliable ?virtual engine development? is a need that represents one of the greatest challenges. Marco Chiodi presents an innovative 3D-CFD-tool, exclusively dedicated and optimized for the simulation of internal combustion engines. Thanks to improved or newly developed 3D-CFD-models for the description of engine processes, this tool ensures an efficient and reliable calculation also by using coarse 3D-CFD-meshes. Based on this approach the CPU-time can be reduced up to a factor 100 in comparison to traditional 3D-CFD-simulations. In addition an integrated and automatic ?evaluation tool? establishes a comprehensive analysis of the relevant engine parameters. Due to the capability of a reliable ?virtual development? of full-engines, this fast response 3D-CFD-tool makes a major contribution to the engine development process.